Employing Lead Thiocyanate Additive to Reduce the Hysteresis and Boost the Fill Factor of Planar Perovskite Solar Cells. Issue 26 (4th May 2016) - Ke, Weijun; Xiao, Chuanxiao; Wang, Changlei; Saparov, Bayrammurad; Duan, Hsin‐Sheng; Zhao, Dewei; Xiao, Zewen; Schulz, Philip; Harvey, Steven P.; Liao, Weiqiang; Meng, Weiwei; Yu, Yue; et al.
Abstract : Lead thiocyanate in the perovskite precursor can increase the grain size of a perovskite thin film and reduce the conductivity of the grain boundaries, leading to perovskite solar cells with reduced hysteresis and enhanced fill factor. A planar perovskite solar cell with grain boundary and interface passivation achieves a steady‐state efficiency of 18.42%.